Cultural Competence and the Higher Education Sector Australian Perspectives, Policies and Practice - Frawley, Jack.; Russell, Gabrielle; Sherwood, Juanita; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2020)
This open access book explores cultural competence in the higher education sector from multi-disciplinary and inter-disciplinary perspectives. It addresses cultural competence in terms of leadership and the role of the higher education sector in cultural competence policy and practice. Drawing on lessons learned, current research and emerging evidence, the book examines various innovative approaches and strategies that incorporate Indigenous knowledge and practices into the development and implementation of cultural competence, and considers the most effective approaches for supporting cultural competence in the higher education sector. This book will appeal to researchers, scholars, policy-makers, practitioners and general readers interested in cultural competence policy and practice.
Part I Introduction -- 1 Cultural Competence and the Higher Education Sector: A journey in the academy -- Part II Perspectives -- 2 The "Culture" in Cultural Competence -- 3 Reflecting on a Way of Being: Anchor principles of cultural competence -- 4 Locating Human Rights in the Cultural Competence Context -- 5 On the Critical, Morally Driven, Self-Reflective Agents of Change and Transformation: A literature review on culturally competent leadership in higher education -- 6 Beliefs, Events and Values Inventory Assessment of Global Identity: Implications and applications for international, cross-cultural and transformative learning -- Part III Policy and Policy Issues -- 7 Evaluating Cultural Competence in Indigenous Higher Education Contexts in Australia: A challenge for change -- 8 Indigenist Leadership in Academia: Towards an aspirational model of mindful servant leadership -- 9 Racism a Social Determinant of Indigenous Health: Yarning about cultural safety and cultural competence strategies toimprove indigenous health -- 10 Healing Mainstream Health: Building understanding and respect for indigenous knowledges -- 11 History in the Now: Asserting indigenous difference in "Top End" higher education using culturally responsive pedagogy -- Part IV Practice and Programs -- 12 The Sydney Language on our Campuses and in our Curriculum -- 13 Students and Academics Working in Partnership to Embed Cultural Competence as a Graduate Quality -- 14 Embedding Cultural Competence in Science Curricula -- 15 Embedding Cultural Competence in Faculty: A mixed-methods evaluation of an applied indigenous proficiency workshop -- 16 An Indigenous Australian Cultural Competence Course: Talking culture, race and power -- 17 "Learning Through Reflection" - Enhancing culturally proficient learning communities in midwifery practice and education: An experience-based learning journey in London, United Kingdom -- Part V Conclusion -- 19 Future Directions: Cultural competence and the higher education sector.
Keywords: Education, Higher; Education and state; Educational sociology; Higher Education; Educational Policy and Politics; Sociology of Education